Connectives in the World Wide Web Arabic Corpus - Hassan, Haslina; Mat Daud, Nuraihan; Atwell, Eric (IDOSI Publication, 2013)
This study analyses the use of connectives in the World Wide Arabic corpus of selected Gulf countries. The corpus was made up of words from selected Arabic sites based on Arabic seed-words which are parallel to English. A quantitative method was employed in analysing the Arabic connectives extracted from the word lists prepared using SketchEngine. The results revealed that connectives, particularly huruf al-jar (prepositions), were on the top ten list for the most frequent words used in all corpora irrespective of country and genre. The study also shows that some of the connectives that are commonly taught in Arabic language classes are not found in the corpus.